Tract-Specific Relationships Between Cerebrospinal Fluid Biomarkers and Periventricular White Matter in Posthemorrhagic Hydrocephalus of Prematurity. Issue 3 (11th December 2020) - Morales, Diego M; Smyser, Christopher D; Han, Rowland H; Kenley, Jeanette K; Shimony, Joshua S; Smyser, Tara A; Strahle, Jennifer M; Inder, Terrie E; Limbrick, David D
Abstract: BACKGROUND: Posthemorrhagic hydrocephalus (PHH) is associated with neurological morbidity and complex neurosurgical care. Improved tools are needed to optimize treatments and to investigate the developmental sequelae of PHH. OBJECTIVE: To examine the relationship between diffusion magnetic resonance imaging (dMRI) and cerebrospinal fluid (CSF) biomarkers of PHH. METHODS: A total of 14 preterm (PT) infants with PHH and 46 controls were included. PT CSF was collected at temporizing surgery in PHH infants (PHH PT CSF) or lumbar puncture in controls. Term-equivalent age (TEA) CSF was acquired via implanted device or at permanent CSF diversion surgery in PHH (PHH-TEA-CSF) or lumbar puncture in controls. TEA dMRI scans were used to measure fractional anisotropy (FA) and mean diffusivity (MD) in the genu of corpus callosum (gCC), posterior limb of internal capsule (PLIC), and optic radiations (OPRA). Associations between dMRI measures and CSF amyloid precursor protein (APP), neural cell adhesion-1 (NCAM-1), and L1 cell adhesion molecule (L1CAM) were assessed using Pearson correlations. RESULTS: APP, NCAM-1, and L1CAM were elevated over controls in PHH-PT-CSF and PHH-TEA-CSF. dMRI FA and MD differed between control and PHH infants across all tracts. PHH-PT-CSF APP levels correlated with gCC and OPRA FA and PLIC MD, while L1CAM correlated with gCC and OPRA FA. In PHH-TEA-CSF, only L1CAM correlated with OPRA MD. CONCLUSION: Tract-specific associations were observed between dMRI and CSF biomarkers at the initiation of PHH treatment. dMRI and CSF biomarker analyses provide innovative complementary methods for examining PHH-related white matter injury and associated developmental sequelae.